Figurative Language in Karla Kukin’s Children Poems (1980) with Surrounding and Animals Theme - Marta Rotua Sitohang; Leni Marlina (English Language and Literature, 2023)
Figurative language is a way of conveying a message using the beauty of language. The use of figurative language is usually found in casual conversation, novels, poems, song lyrics, speech, and poems. This study aims to investigate the types of figurative language in selected children’s poetry compiled by Sylvia M. Vardell (2020). This research focused on the types of figurative language and the meaning of those figurative lines. The method of this research is the descriptive qualitative method.  The object of this research is the figurative lines from selected 5 poems with Family and Friends theme. The researcher also made a conclusion about the most frequent types at the end. To achieve the goal of this research, the researcher employed the theory from Laurence E. Rozakis (1995) about the types of figurative language. Thus, from 43 data, the findings show that there are 12 occurrences of hyperbole, 18 occurrences of metaphor, 1 occurrence of simile, 2 occurrences of ambiguity, 5 occurrences of personification, three occurrences of synecdoche, and 2 occurrences of allegory. The researcher finds a conclusion about the most dominant type in this research, which is metaphor.